2003
DOI: 10.1097/00006324-200306000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Intraocular Pressure and Pulsatile Ocular Blood Flow in a Young Normal Population

Abstract: This study confirms the hypotensive effect of exercise on intraocular pressure and shows that exercise significantly increases pulsatile ocular blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
2
37
0
1
Order By: Relevance
“…17,18 The reduction in OPA was found to be moderately associated with the changes in pulse rate after exercise, indicating that as the pulse rate increases, the OPA decreases. This implies that exercise induced increases in pulse rate are associated with a decrease in pulse volume (as the change in IOP with each pulse decreased as pulse rate increased), as has been previously documented.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…17,18 The reduction in OPA was found to be moderately associated with the changes in pulse rate after exercise, indicating that as the pulse rate increases, the OPA decreases. This implies that exercise induced increases in pulse rate are associated with a decrease in pulse volume (as the change in IOP with each pulse decreased as pulse rate increased), as has been previously documented.…”
Section: Discussionmentioning
confidence: 94%
“…[17][18][19][20] Lovasik et al 19 reported a significant increase of choroidal blood flow of 5-6% during a period of dynamic exercise. Although choroidal blood flow was not measured in this study, a small magnitude increase in this parameter would be expected to lead to expansion of the choroid, and an accompanying reduction in AXL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especificamente é importante ressaltar que esses indiví-duos praticam atividade física de alta intensidade regularmente, no mínimo a seis meses, assim sendo, de acordo com autores (11) é observado redução na PIO fora dos exercícios, tanto de indivíduos normais quanto de suspeitos de glaucoma, após 3 a 6 meses do início de um programa de exercícios aeróbios, com retorno aos níveis pré-exercício da PIO, 3 semanas após a interrupção dos exercícios, revelando também nesse aspecto um dos princípios do treinamento desportivo, conhecido como destreinamento.…”
Section: Discussionunclassified
“…The effect of exercise on IOP has been well studied [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Although the majority of studies agree that dynamic exercise produces a decrease in IOP [8][9][10][11][12][13], no consensus was found for the effect of isometric exercise (i.e., static strength training where the joint angle and muscle length do not change during the contraction).…”
Section: Introductionmentioning
confidence: 99%